A comprehensive periodontal treatment project: The periodontal status, compliance rates, and risk factors - Kuo-Ching Huang; Chao-Han Lai; Chiung-Fang Huang; Hsein-Kun Lu (Journal of Dental Sciences, 2016)
Background/purpose: The comprehensive periodontal treatment project (CPTP) is being implemented in Taiwan since 2010. This retrospective study compared the periodontal status, compliance rates, and influence of risk factors for periodontal recurrence and tooth loss among groups of patients who accepted CPTP and conventional periodontal treatment (CPT). Materials and methods: A total of 161 patients who received periodontal therapy were investigated and divided into compliant (n = 94) and noncompliant (n = 67) groups. Patients in the compliant group were further assigned to two subgroups: CPT with a postcard recall (PR) system (CPT + PR, n = 48) and CPTP with a PR system (CPTP + PR, n = 46). Demographic characteristics and periodontal parameters, including the probing pocket depth (PPD), bleeding on probing (BOP), and plaque control record (PCR), were collected for comparison between the subgroups. The risk factors for periodontal recurrence and tooth loss were statistically analyzed. Results: The 161 patients were followed-up for a mean of 3.8 years. The patients in the CPTP + PR subgroup exhibited shallower PPD, less BOP, improved PCR, and fewer tooth loss. Age, smoking, PPD ≥7 mm, and PCR ≥30% were associated with periodontal recurrence, whereas age, diabetes, BOP ≥30%, and duration of the follow-up period were correlated with tooth loss. PR apparently increased the compliance rate of patients (27.3% vs. 77.7%). Conclusion: CPTP with PR led to an optimal and stable periodontal status in patients. Compliant patients maintained a significantly improved periodontal status as compared with noncompliant patients.